Risk factors for pancreatitis: a literature review - Martínez, Glendy Alejandra (International Journal Of Community Medicine And Public Health, 2023)
Pancreatitis is an inflammatory disease of the pancreas that can have serious consequences for the health of patients. Understanding the risk factors associated with this condition is critical to its prevention, early diagnosis, and proper treatment. In this literature review article, we present a synthesis of the updated scientific literature on the risk factors for pancreatitis, their epidemiology, clinical significance, diagnosis, surgical treatment, complications and a discussion on the clinical implications of these findings. In addition, it concludes by highlighting the importance of identifying and addressing these risk factors in a comprehensive manner to improve the management of this disease.